Pelaksanaan Unit Usaha Mikro Kecil Menengah (UMKM) Menurut Hukum Islam di Indonesia - Yoga Perdata, Randhika (UNES Law Review, 2023)
Micro, Small and Medium Enterprises (MSMEs) are independent productive business units carried out by individuals or business entities in all economic sectors. To fulfill life's needs to be prosperous, people who have the ability and are keen to see their potential and can identify the environment, can find opportunities and open up business opportunities for the community. Efforts to fulfill living needs include conducting Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a vital role in reducing poverty because the existence of MSMEs can open up large employment opportunities thereby improving the welfare of the people. The aim of this research is to find out the concept of UMKN by sharia. The type of research used in this research is normative legal research. The data collection technique was carried out using a library study. The research results will show MSMEs from the perspective of Islamic law.